A study on the acceptance and use of Facebook application for academic purposes / Muhammad Nafis Azahar - Azahar, Muhammad Nafis (Faculty of Business and Management, 2019)
'Facebook' application has been broadly utilized among clients around the globe. In any case, in academic purposes, numerous individuals don't perceive its utilization, particularly in Malaysia. This research along these lines plans to research the connection between three independent variables the acceptance and utilization of 'Facebook' application for academic reasons among students in Bandaraya Melaka and also students in Melaka. In this research, the specialist utilized three variables, which are performance expectancy, effort expectancy, and social influence, as proposed in the Unified Theory of Acceptance and Use of Technology. This research will be utilized survey as the exploration instrument and were dispersed to 150 students. The finding is then investigated and demonstrated that exertion anticipation and social impact are not identified with the reliant variable. This study additionally reasoned that performance expectancy is the hugest factor added to acceptance and use of 'Facebook' application for academic purposes among students.